Save Steve - Hendriks, Jenni; Caplan, Ted (HarperTeen, 2020)
"Steve Stevenson is a jerk. That might not be a cool thing to say about someone with cancer, but it's true. Yeah, he throws legendary parties and is the most popular guy in school, but he also loves humiliating pranks and Cardi B, and he doesn't recycle. Worst of all, he's dating Kaia - the girl of nice guy Cam's dreams. But when a desperate Kaia asks Cam to help her raise money to pay for Steve's experimental treatment, Cam offers to organize the biggest, most viral fundraising campaign. Maybe then Kaia will finally see Cam as the perfect, thoughtful, altruistic, good guy for her." --